A Rare Case of Cervical Charcot After Spinal Cord Injury: A Case Report. Issue 4 (October 2019) - Davidson, Iyooh U; Quinones, Daniel J.; Haines, Colin M.; Kilgore, Kevin L.; Keith, Michael W.; Moore, Timothy A.
Abstract : Case: We present a rare case of cervical Charcot disease that was diagnosed in a paraplegic patient by loss of function caudal to the original level of spinal cord injury. Clinical imaging, diagnosis, differentials, and operative management are discussed. Conclusions: Charcot disease of the cervical spine is rare and very difficult to diagnose in the paraplegic patient population. High clinical suspicion should be maintained in these patients who demonstrate any form of neurologic deterioration, mechanical instability, or change in spinal alignment. It is often necessary to rule out infection. Spinal decompression and surgical stabilization is the treatment of choice.